Can Liposomal Bupivacaine Be Safely Utilized in Elective Spine Surgery?. Issue 2 (April 2019) - Brown, Luke; Weir, Tristan; Koenig, Scott; Shasti, Mark; Yousaf, Imran; Yousaf, Omer; Tannous, Oliver; Koh, Eugene; Banagan, Kelley; Gelb, Daniel; Ludwig, Steven
Study Design: Single-blinded prospective randomized control trial. Objectives: To compare the incidence of adverse events (AEs) and hospital length of stay between patients who received liposomal bupivacaine (LB) versus a single saline injection, following posterior lumbar decompression and fusion surgery for degenerative spondylosis. Methods: From 2015 to 2016, 59 patients undergoing posterior lumbar decompression and fusion surgery were prospectively enrolled and randomized to receive either 60 mL injection of 266 mg LB or 60 mL of 0.9% sterile saline, intraoperatively. Outcome measures included the incidence of postoperative AEs and hospital length of stay. Results: The most common AEs in the treatment group were nausea (39.3%), emesis (18.1%), and hypotension (18.1%). Nausea (23%), constipation (19.2%), and urinary retention (15.3%) were most common in the control group. Patients who received LB had an increased risk of developing nausea (relative risk [RR] = 1.7; 95% confidence interval [CI] = 0.75-3.8), emesis (RR = 2.3; 95% CI = 0.51-10.7), and headaches (RR = 2.36; 95% CI = 0.26-21.4). Patients receiving LB had a decreased risk of developing constipation (RR = 0.78; 95% CI = 0.25-2.43), urinary retention (RR = 0.78; 95% CI = 0.21-2.85), and pruritus (RR = 0.78; 95% = 0.21-2.8) postoperatively. Relative risk values mentioned above failed to reach statistical significance. No significant difference in the hospital length of stay between both groups was found (3.9 vs 3.9 days; P = .92). Conclusion: Single-dose injections of LB to the surgical site prior to wound closure did not significantly increase or decrease the incidence or risk of developing AEs postoperatively. Furthermore, no significant difference was found in the hospital length of stay between both groups.